(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
The purpose of the article is to study the prospects for the introduction of digital services in commercial banks, to study ways to successfully introduce digital technologies for commercial banks, improve customer service, and increase the overall efficiency of banks. In today’s digital economy, the introduction of digital services for banks serves not only as a convenience, but also as an important factor ensuring competitiveness. Digital technologies open up new opportunities for banks, create convenience for customers, and reduce operating costs